Effective Team Management with VSTS and TFS A Guide for Scrum Masters - Chandrasekara, Chaminda (Apress, 2018)
Gain the essential knowledge to use VSTS/TFS effectively to empower your Agile teams. This book provides a deep analysis into issues Agile teams may face and how to overcome them by adopting and implementing the proper tools. Rather than just review VSTS/TFS features, this book provides proven solutions to the challenges in building better Agile teams. You'll see how to handle small teams and how to facilitate large teams to support large scale projects. You'll also learn to work with distributed teams in different geo locations, which will deepen your ability to get successful project/product outcomes from your teams. Special focus is given to creating long term sustainability to effectively manage a backlog/portfolio backlog. You'll explore how to work with stakeholders closely to better understand a project's requirements and review how to perform the post execution analysis and planning for next development cycle and forecasting.